Integration of Geographic Information Systems in the Economic Valuation Analysis of Food Crops in Bleberan Village - Muhammad Miftahurridlo; Zulfajri Zulfajri; Nur Hasanah; Darliandri Darliandri; Rohil Al Azizah (Unversitas Muhammadiyah Mataram, 2026)
The agricultural sector is a mainstay of the Indonesian economy, yet it faces serious challenges in the form of a nationwide decline in cultivated land area. This study aims to examine the state of food crop agriculture, identify the benefits derived by the community, and analyze the Total Economic Value (TEV) of agricultural activities in Bleberan Village, Playen Subdistrict, Gunungkidul Regency. The research method used is quantitative descriptive with an economic valuation approach. Data collection was conducted through observation, documentation, and interviews with 100 farmer respondents selected using the Slovin formula. Data analysis includes the calculation of direct utility value, indirect utility value, option value, and existence value. The results of the study indicate that agricultural activities in Bleberan Village are divided into three main phases: pre-planting, planting, and post-harvest, with corn as the flagship commodity due to its adaptation to dry land. The Total Economic Value (TEV) of food crop agricultural activities in Bleberan Village reached Rp 2,584,508,776. This value consists of direct benefits of Rp 1,493,057,500, indirect benefits of Rp 1,089,829,596 (including oxygen-producing and carbon-absorbing functions), choice value of Rp 468,840, and existence value of Rp 1,152,840. These findings confirm that the economic benefits of agriculture extend far beyond the mere market value of commodities, encompassing ecosystem services and existential values that are crucial to the sustainability of the region.